Thapsigargin Amplifies the Platelet Procoagulant Response Caused by Thrombin - Smeets, E F; Heemskerk, J W M; Comfurius, P; Bevers, E M; Zwaal, R F A (Thrombosis and Haemostasis, 1993)
The platelet procoagulant response involves an increase in surface-exposed phosphatidylserine, which allows binding and assembly of enzyme complexes of the coagulation pathway resulting in acceleration of the clotting process. This response essentially requires the presence of extracellular Ca2+, and varies in extent with the type of agonist used. In the present paper we demonstrate that the moderate procoagulant response of human platelets caused by thrombin is strongly amplified by the presence of thapsigargin, an inhibitor of the microsomal Ca2+-ATPase. Thapsigargin, like thrombin, has only a weak effect on procoagulant activity. The large increase in procoagulant activity observed with the combined action of these two agonists is associated with increased shedding of microvesicles from the platelet plasma membrane as well as with inhibition of transport of a fluorescent-labeled analog of phosphatidylserine from the outer to the inner leaflet of the plasma membrane by the aminophospholipid translocase. The latter two observations support current concepts regarding the mechanism of development of procoagulant activity.Although the synergistic effect of thapsigargin on thrombin-induced procoagulant activity is at least in part due to the high levels of intracellular [Ca2+] evoked by these agonists, the data clearly indicate that a rise of the intracellular [Ca2+] is insufficient to completely explain this response. The present findings suggest that additional factors control expression of procoagulant activity upon stimulation of platelets by thrombin.